PENGARUH RETURN ON ASSET DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN - Gismi Salita; Novera Martiliva (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to find out and analyze how much influence Return On Assets and Current Ratio have on stock prices in food and beverage companies listed on the Indonesia Stock Exchange in 2016-2021. This type of research is quantitative research, the type of data is secondary data accessed through the official website of the Indonesia Stock Exchange (www.idnfinancial.com). The sample for this research was taken from 10 food and beverage companies listed on the Indonesia Stock Exchange in 2016-2021 using a purposive sampling technique. The method used in this study uses descriptive statistical tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of this study partially show that Return On Assets has no significant effect on stock prices and the current ratio has a significant effect on stock prices.